The Impact of Social Websites over Jordanian Students’ Intentions of Active political Participation: An Application of Theory of Planned Behavior. - Al-Mohammad, Samer M. (International Review of Management and Marketing, 2017)
Appreciating the massive popularity and application of social websites worldwide, the purpose of this paper was to explore the impact of such websites over young Jordanians’ intentions of active political participation. To that end, the paper developed a model based on Ajzen’s (1991) Theory of Planned Behavior. Further, quantitative data was collected through a survey of 461 BA students at one Jordanian university. Empirical findings underlined that respondents’ use of social websites had a direct impact over their exposure to online political content. Further, exposure to such content had a direct impact over respondents’ both “attitudes towards active political participation” and “perceived behavioral control”. While “subjective norms” had also a strong significant impact over respondents’ “attitudes towards active political participation” and “perceived behavioral control”, both constructs had a direct impact over respondents’ “intentions of active political participation”. Upon its findings, the paper draws some conclusions, introduces certain recommendations, and suggests further avenues for future research. Keywords: Active Political Participations, Social Websites, Theory of Planned Behavior. JEL Classifications: M30, M31.